(untitled) - Moore, Steve (Hoboken, N.J., 2006)
The Encyclopedia of Commodity and Financial Spreads is divided by product category-energy, natural gas, meats, soybeans, corn/wheat, currencies, interest rates, and metals. The precise performance of each spread is identified-over the previous 20 years-and combined with a graph that displays visually the price performance of the spread. For each of the 175 trades identified, there is an explanation of the trade, its history, and advice on how traders should approach the trade.
Keywords: Speculation,Investment analysis,Tương lai,Dự đoán,Phân tích đầu tư,Futures